Religion and Religiosity in Russia: An Overview. (July 2016) - Upadhyay, Archana
The collapse of the USSR marked the end of the multiethnic 'Soviet Nation'. Consequent to the moving out of the republics from the federation, Russia and Russians faced the challenge of defining their own identity and that of a new, multinational, multi-confessional state—the Russian Federation. Towards this end of regenerating identity, religion proved to be a very potent instrument. Religion and religiosity in Russia is closely interconnected with ethnic self-awareness and consolidation of political identities that go beyond religion. It has been employed to foster both inclusive and exclusive identities and have also impacted crucial decisions of the state. Its social and political role is profound and so is its engagement with the institutions of the state. It is significant that both the institutional and ideological aspects of religion have emerged as distinct factors in contemporary Russian politics. The re-emergence and the consolidation of the Russian Orthodox Church (ROC) in the social and political life of contemporary Russia has submerged smaller religious identities in all spheres of social and political life. Given Russia's religious diversity, this has impacted intergroup relations and generated tensions in the society, resulting from both the 'politicization of religion' and the 'desecularization' project from above.